2006
DOI: 10.1007/s00535-006-1876-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of nonalcoholic steatohepatitis in Japan: evidence from the literature

Abstract: Metabolic syndrome, that is, obesity, hypertension, hyperlipidemia, and insulin resistance with hyperinsulinemia, is a new disease entity prevailing worldwide, and nonalcoholic steatohepatitis (NASH) is believed to be a hepatic expression of this syndrome. NASH is characterized by zone 3-dominant hepatic steatosis with ballooned hepatocytes and Mallory bodies, zone 3 pericellular and perivenular fibrosis with or without bridging fibrosis, and lobular inflammatory cell infiltration. Indeed, 90% of NASH has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 98 publications
3
42
1
Order By: Relevance
“…Causes of hypopituitarism are shown in Supplementary Figure 1A, see section on supplementary data given at the end of this article. The prevalence of NAFLD in the control group (12% overall, men 18%, women 7%) was comparable with that in the previous report in the Japanese population (22,23,24). Strikingly, the prevalence of NAFLD in the GHD group was significantly increased by 6.4-fold compared with the control group (77 and 12%, P!0.001; Table 1).…”
Section: The Prevalence Of Nafld/nash In Adult Hypopituitary Patientssupporting
confidence: 86%
See 1 more Smart Citation
“…Causes of hypopituitarism are shown in Supplementary Figure 1A, see section on supplementary data given at the end of this article. The prevalence of NAFLD in the control group (12% overall, men 18%, women 7%) was comparable with that in the previous report in the Japanese population (22,23,24). Strikingly, the prevalence of NAFLD in the GHD group was significantly increased by 6.4-fold compared with the control group (77 and 12%, P!0.001; Table 1).…”
Section: The Prevalence Of Nafld/nash In Adult Hypopituitary Patientssupporting
confidence: 86%
“…Because liver biopsy was performed in only a part of the group, it is speculated that the prevalence of NASH in the hypopituitary patients with GHD was estimated to be lower than that of the true one. Nonetheless, the prevalence of NASH in this study (14/66, 21%) was apparently high compared with the prevalence of 1-3% that was previously reported for the Japanese population (24,25).…”
Section: The Prevalence Of Nafld/nash In Adult Hypopituitary Patientscontrasting
confidence: 75%
“…The frequency of fatty liver is higher in men than in women and is most commonly found in patients with excessive alcohol intake and excessive intake of carbohydrates 41) . In those aged less than 20 years, the frequency of fatty liver is approximately 20% in men and 5% in women 42) ; however, in our study, hepatorenal echo contrast positivity, regardless of obesity, was found in 23.3% of boys (32 participants) and 30.4% of girls (55 participants).…”
Section: Fatty Livermentioning
confidence: 99%
“…Based on annual health checks, the prevalence of fatty liver diagnosed by ultrasonography increased from 10% in 1980 to 20-40% in 2000 among adults. Thus, nonalcoholic fatty liver disease (NAFLD) is now emerging as the most common liver disease in Japan (2,3). The recent worldwide rise in the number of patients with nonalcoholic steatohepatitis (NASH) tends to parallel the increase in metabolic syndrome, which includes obesity, type 2 diabetes and hyperlipidemia (4).…”
Section: Introductionmentioning
confidence: 99%